Influence of the elevated ambient temperature on immunoglobulin G and immunoglobulin G subclasses in sera of Wistar rats - Jurhar-Pavlova Maja; Petlichkovski Aleksandar; Trajkov Dejan; Efinska-Mladenovska Olivija; Arsov Todor; Strezova Ana; Dinevska-Kjovkarova Suzana; Mitev Slavcho; Spiroski Mirko (Vojnosanitetski Pregled)
The aim of our research was to examine changes in the immune system of the rats influenced by the elevated ambient temperature. Male Wistar rats were divided, into 2 groups and housed at 20 ± 2°C (n=64, control group) and 35 ± 1°C (n=74, experimental group), during precise timing of 1, 4, 7, 14, 21, and 30 days. All the animals were given food and water ad libitum, and were lighted during 12 hours per day. We have measured IgG, IgG1, IgG2a, IgG2b and IgG2c. The obtained results showed significant elevation in the level of IgG after 4 and 7 days (+32%), IgG2a after 7th (+88%), 14th and 21nd day (+110%), IgG2b after 14 days (+60%) at 35 ± 1°C compared with the control group at 20 ± 2°C. IgG1 level was not affected and IgG2c showed significant decrease after 21st day at 35 ± 1°C. In conclusion, during the elevated ambient temperature the immune system is activated as one of the regulation mechanisms in homeostasis and survival of the population.